Hypertensive crisis in children: an experience in a single tertiary care center in Korea. Issue 1 (December 2016) - Lee, Geum; Lee, I; Park, Se; Kim, Ji; Oh, Ji; Shin, Jae
Abstract Background Hypertensive crisis is a medical emergency that can cause acute damage to multiple end-organs. However, relatively little is known on the etiology, treatment, and outcomes of hypertensive crisis in Korean children. The aim of this study was to determine the etiologies and efficacy of drugs for hypertensive crisis in children during the past 5 years at a single center in Korea. Methods We analyzed data from 51 children with hypertensive crisis during the period between January 1, 2010 and April 1, 2014. The patients were divided into two groups: those diagnosed with a hypertensive emergency (hypertension with organ injury, n = 31) and those diagnosed with a hypertensive urgency (hypertension without organ injury, n = 20). Baseline etiologies and risk factors were compared between the two groups. In addition, systolic and diastolic blood pressures were evaluated at 1, 2, 4, and 5 hours after the administration of intravenous antihypertensive drugs. Results Kidney injury and cancer were the common causes in patients with hypertensive crisis. Cardiovascular complications (cardiac hypertrophy) (p = 0.002), central nervous system complications (p = 0.004), and retinopathy (p = 0.034) were more frequently observed in children with hypertensive emergency than those with hypertensive urgency. However, the proportion of renal complications was similar in both groups. Hydralazine was most commonly used in both groups to control acute increasing blood pressure at first. However, it was often ineffective for controlling abrupt elevated blood pressure. Therefore, intravenous antihypertensive drugs were changed from hydralazine to nicardipine, labetalol, or nitroprusside to control the high blood pressure in 45.1 % of the patients. Particularly, in patients with hypertensive crisis, there was no significant difference in reduction of systolic and diastolic blood pressure and in improvement of clinical outcomes between nicardipine and labetalol administration. Conclusion Close blood pressure monitoring and careful examinations should be mandatory in children with underlying disease, especially renal diseases and cancer. Furthermore, both nicardipine and labetalol may be effective antihypertensive drug in lowering high blood pressure in children with hypertensive crisis.